Impact of humic acid on the accumulation of metals by microalgae - Kováčik, Jozef; Bujdoš, Marek; Babula, Petr (Environmental science and pollution research international, 2018)
Indirect impact of humic acid (HA) on metal accumulation and toxicity (Cd, Ni, Pb, and Hg; 100 μM; 24 h of exposure) in Scenedesmus quadricauda was studied. Algae were pre-cultured on solid (10 and 100 mg HA/L) or in liquid media (1, 5, and 10 mg HA/L) over 30 days and then exposed to metals mentioned above. Accumulation of applied metals irrespective of pre-culture increased in the order Ni < Cd < Pb < Hg. Algae pre-cultured on solid HA-enriched media accumulated more Cd (+ 46% at 10 mg HA/L), Ni (+ 50 and + 81% at 10 and 100 mg HA/L, respectively), and Pb (+ 15% at 100 mg HA/L) but the impact on Hg amount was not detected. Potassium and calcium decreased in response to all metals (K strongly under Hg excess) and HA had negligible impact. Interestingly, fluorescence microscopy detection of reactive oxygen species/nitric oxide (ROS/NO) balance showed that HA pre-culture suppressed ROS signal and stimulated NO signal in response to Cd (indicating positive impact of HA) while ROS signal in Ni and Pb treatments rather increased but NO signal decreased as expected from elevated Ni and Pb accumulation. Hg had clearly the most toxic impact on the ROS/NO balance. Algae pre-cultured in liquid HA-enriched media showed significantly increased Ni accumulation only (+ 14% at a dose 10 mg HA/L). Present study for the first time showed that humic acid may indirectly affect accumulation of metals and that solid HA-enriched medium used for pre-culture is more suitable to increase accumulation of metals by algae.
Keywords: mikrořasy; Microscopy, Fluorescence; Oxidative Stress; Scenedesmus; reaktivní formy kyslíku; Metals, Heavy; oxidační stres; huminové látky; Dose-Response Relationship, Drug; fluorescenční mikroskopie; Reactive Oxygen Species; testy akutní toxicity; těžké kovy; Humic Substances; Water Pollutants, Chemical; vztah mezi dávkou a účinkem léčiva; Microalgae; Toxicity Tests, Acute; chemické látky znečišťující vodu